NILAI EKONOMI WISATA TAMAN KOTA BERDASARKAN METODE BIAYA PERJALANAN (Travel Cost Methode) DI PEKANBARU - Bayu Dewanto; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Green Open Space (GOS) is important part of the city structure forming. One of city which need to attention of city park as part of GOS is Pekanbaru City. Pekanbaru is crowded enough city, buildings and vehicle already crowded city streets. The existence of a Pekanbaru city park can reduce air pollution, so that making the city atmosphere become more beautiful and naturally. City Park also used as recreation area as well as being one of the socializing media for population in Pekanbaru City, because there is hardly any place which has a sense of comfort and far from pollution. The purpose of this research is find out the characteristic of visitors who came for recreation to Pekanbaru City Park, to know how much economic value tour of Pekanbaru City Park per year based on Travel Cost Methode (TCM), to find out the factors affecting of economic value based on Travel Cost Methode (TCM). Materials and objects of this research is questionnaire sheet. Data collected using SPSS 19 (Statistic Package For Social Science) analyze. The results showed that Pekanbaru city park economic value based on Travel Cost Methode (TCM) of Rp.967.770.636/year, with average person of Rp.22.095,22. Keywords : Economic Value , Cost Travel, Park City